Studying Supply Chain and Tourism Cluster Development - Olga V. Skrobotova; Raisa M. Ivanova; Irina E. Polyakova; Galina Y. Karaseva (International Journal of Supply Chain Management, 2019)
Supply chain and tourism cluster are the two important ways to enhance the competitiveness of regions or industries. By discussing the differences and links between the two, this paper concludes that tourism cluster and supply chain carry features of compatibility and symbiosis. The importance of this research paper is determined by the fact that a significant number of tourism clusters established in the territory of the Russian Federation are not always successful as catalysts for the tourism sector development. This study aims to determine methods for conducting research on specialization as a factor in tourism cluster development, taking into consideration the existing research approaches and findings in this area. The systemic, structural, functional and analysis methods were used, along with a general theoretic approach to researching tourism cluster development. The selected methods made it possible to identify approaches to forming the relevant research methodologies. Based on the presented approaches, it is possible to choose research methods and the coherence of research activities in this area, with a view to identify key development indicators for tourism development and various tourism-related processes taking place within the territory of a tourism cluster. The research findings will provide necessary tools and mechanisms for developing tourism clusters based on the diversification of their specialization. The findings of the study are directed at increasing the effectiveness of decisions taken to assess and forecast tourism cluster development and can also be of use to all those interested in this field. The materials of the present study can be used by regional administrations to monitor and make effective management decisions aimed at improving regional tourism development programs. Experts and scholars could also benefit from the findings of this study to analyze and develop projections and to promote topic-related methodological approaches. The article will be of practical value for the specialists in tourism planning, tourism administration and tourism enterprise managers.